Adherence as a predictor of dropout in Internet‐based guided self‐help for adults with binge‐eating disorder and overweight or obesity. Issue 4 (31st December 2019) - Puls, Hans‐Christian; Schmidt, Ricarda; Herpertz, Stephan; Zipfel, Stephan; Tuschen‐Caffier, Brunna; Friederich, Hans‐Christoph; Gerlach, Frauke; Mayr, Andreas; Lam, Tony; Schade‐Brittinger, Carmen; de Zwaan, Martina; Hilbert, Anja
Abstract: Objective: Internet‐based guided self‐help (GSH‐I) is an efficacious treatment for adults with binge‐eating disorder (BED) and overweight or obesity. Although broadly accessible, high dropout from GSH‐I has been reported. However, little is known about the factors explaining dropout from GSH‐I, including patients' adherence to treatment. Method: Within a randomized trial on the treatment of BED, adherence to 4‐month GSH‐I was objectively assessed in N = 89 patients with BED and overweight or obesity. Objective adherence and subjective treatment evaluation were evaluated as predictors of dropout from GSH‐I, defined as having accessed 5 or less of 11 modules. Cutoffs with optimal sensitivity and specificity were derived using Receiver Operating Characteristics curves analysis, and baseline sociodemographic and clinical correlates were determined. Results: According to our definition, n = 22 (24.7%) patients were defined as dropouts. Results of the full logistic regression model accounted for 72% of the variance in dropout and all objective adherence parameters (i.e., number of messages exchanged, days with a completed food diary, and days spent per module), but not patients' subjective GSH‐I evaluation significantly predicted dropout. Specifically, not completing the food diary in week 7 had maximized sensitivity and specificity in predicting dropout. Patients' body mass index was positively associated with the number of messages exchanged between patients and coaches. No other associations between baseline variables and objective adherence were found. Discussion: Patients at risk for dropout from GSH‐I can be reliably identified via monitoring of objective adherence and may be provided with additional interventions to prevent dropout.